Yabancılara Türkçe Öğretiminde Etkinlikler - A1 - A2 - Er, Onur; Aramak, Kürşat; Özden, Esra; Yazıcı, Muhammet Hüseyin; Biçer, Nurşat; Memiş, Muhammet; Ertürk, Berker; Çıvğın, Hakan; Işık Kobazi, Ayşegül; Yılmaz Karaca, Meryem; İşci Karameşe, Cenan; Çetin, Betül; et al. (2024)
-